2000
DOI: 10.1590/s0100-879x2000000200007
|View full text |Cite
|
Sign up to set email alerts
|

Study of urinary acidification in patients with idiopathic hypocitraturia

Abstract: Hypocitraturia (HCit) is one of the most remarkable features of renal tubular acidosis, but an acidification defect is not seen in the majority of hypocitraturic patients, whose disease is denoted idiopathic hypocitraturia. In order to assess the integrity of urinary acidification mechanisms in hypocitraturic idiopathic calcium stone formers, we studied two groups of patients, hypocitraturic (HCit, N = 21, 39.5 ± 11.5 years, 11 females and 10 males) and normocitraturic (NCit, N = 23, 40.2 ± 11.7 years, 16 fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Therefore, a reduction in serum pH and bicarbonate in patients with HC suggests that the primary factor involved could be a deficiency in intracellular acidification, which is generally present in patients with IH but is more severe in those with HC, as suggested by Araffljo and Rebelo [26].…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, a reduction in serum pH and bicarbonate in patients with HC suggests that the primary factor involved could be a deficiency in intracellular acidification, which is generally present in patients with IH but is more severe in those with HC, as suggested by Araffljo and Rebelo [26].…”
Section: Discussionmentioning
confidence: 91%
“…These findings led the authors to suggest that the presence of a certain degree of intracellular acidosis and/or an increased production of prostaglandin E2 (PGE2) is involved in the mechanism of bone mass reduction in these patients [1]. Araujo and Rebelo [49] also suggested that the primary factor involved in bone mass reduction in those patients could be a deficiency in intracellular acidification, which is generally present in patients with IH, but is more severe in those with hypocitraturia.…”
Section: Other Analysismentioning
confidence: 99%
“…Acquired dRTA frequently develops as a consequence of Gougerot-Sjögren syndrome [8] and other autoimmune diseases [9, 10]. Very few studies have evaluated the utility of screening for a urinary acidification defects in non-acidotic patients with concomitant hypocitraturia, recurrent nephrolithiasis [11, 12], and/or bone demineralization [13, 14]. In the present study, we retrospectively analyzed data from patients with low citrate excretion and nephrolithiasis, nephrocalcinosis, and/or bone demineralization.…”
Section: Introductionmentioning
confidence: 99%